2022
DOI: 10.1186/s13006-021-00443-8
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum women’s views on human milk banking in a city in Southeast China: a cross-sectional survey

Abstract: Background Donor human milk is the best alternative for preterm infants when their mother’s own milk is insufficient or unavailable. The development of human milk banks in China started late, and in most of these banks, the amount of donor human milk is insufficient for clinical demand. Moreover, many mothers are reluctant to use donor human milk due to safety concerns. It is important to understand the potential supply and demand of donor human milk before establishing a new human milk bank. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Believing in the altruistic nature of milk donation has been mentioned in previous studies as the most important factor (Bhoola & Biggs, 2021;Doshmangir et al, 2019). Polish mothers (84.8%) (Smyk et al, 2021) and Chinese mothers (73.4%) (Tu et al, 2022) were willing to donate milk with the most common reason being to help other infants, which is consistent with the findings of the present study. Also, the main reason for unwillingness to donate milk was insufficient breast milk (Tu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Believing in the altruistic nature of milk donation has been mentioned in previous studies as the most important factor (Bhoola & Biggs, 2021;Doshmangir et al, 2019). Polish mothers (84.8%) (Smyk et al, 2021) and Chinese mothers (73.4%) (Tu et al, 2022) were willing to donate milk with the most common reason being to help other infants, which is consistent with the findings of the present study. Also, the main reason for unwillingness to donate milk was insufficient breast milk (Tu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Polish mothers (84.8%) (Smyk et al, 2021) and Chinese mothers (73.4%) (Tu et al, 2022) were willing to donate milk with the most common reason being to help other infants, which is consistent with the findings of the present study. Also, the main reason for unwillingness to donate milk was insufficient breast milk (Tu et al, 2022). It is notable that studies in Islamic countries have reported the poor willingness for milk donation and accepting donated milk due to cultural and religious reasons (Ergin & Uzun, 2018;Özdemir et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations